A modelling-based analysis for fatigue life prediction of SLM printed metal parts due to porosity - Ganesan Ragul (2018)
Additive manufacturing, also known as rapid prototyping or 30 printing, is an emerging technology which can transfer digital data into physical parts. Selective Laser Melting (SLM) is a powder bed additive manufacturing technique which is used to produce parts . However, due to various defects such as pores , probably cracks are formed at different size defects , leading to fatigue failures under cyclic loading. Usually, the fatigue tests are conducted to characterise the relation between fatigue life and porosity. The conventional fatigue analysis is destructive and time-consuming , hence a novel modelling approach is required for an efficient analysis. The objective of the present study is to develop a three-dimensional (30) finite-element model of the parts with pores to study their influence on fatigue life. The twodimensional (20) finite-element model is also used to analyse the stress concentrations around the pores and between pores. The results of the 20 tinite-elernent model show that stress concentration increases when the distance between circular pores decreases, and increases as the size of pore increases. Furthermore , the stress concentration around elliptical pore becomes higher than that of circular one. It is also found that the stress concentration around two adjacent circular pores reaches the maximum when they are oriented at an angle of 30 degrees. Novel modelling techniques to present the pores, such as Young ' s modulus reduction and the element elimination , are integrated into the 30 model of the parts, with pores distribution as obtained from the actual SLM parts. The fatigue analysis is carried out using ABAQUS and Fe-Safe software by Stress-based Brown Miller algorithm. From 30 modelling, it is observed that the fatigue life increases as the porosity fraction decreases. In summary, a technique to model and analyse 30 parts with pores distributed is developed which is non-destructive and less time-consuming. The fatigue life of those parts are studied with different porosity fractions which are obtained from SLM process.